Le rôle du court métrage dans le développement de la compétence interculturelle en classe de français. ( Cas des élèves de la classe de 11ème ) - علي ديب زويا; مروان اسبر (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The short film is considered as an effective document that can be used in a French language class, because we can see a real communicative situation through it. It contains cultural points that cannot be found in other supportive documents, like extra linguistic elements. We suppose in this research that using the short film in a French language class will help improve students’ intercultural competence, by the riches of the cultural points that cannot be found in other videos. The question is: ‘’ How to use the short film to improve intercultural competence?’’